Septic encephalopathy: does inflammation drive the brain crazy? - Dal-Pizzol,Felipe (2014)
Sepsis and the multiorgan dysfunction syndrome are among the most common reasons for admission to an intensive care unit, and are a leading cause of death. During sepsis, the central nervous system (CNS) is one of the first organs affected, and this is clinically manifested as sepsis-associated encephalopathy (SAE). It is postulated that the common final pathway that leads to SAE symptoms is the deregulation of neurotransmitters, mainly acetylcholine. Thus, it is supposed that inflammation can affect neurotransmitters, which is associated with SAE development. In this review, we will cover the current evidence (or lack thereof) for the mechanisms by which systemic inflammation interferes with the metabolism of major CNS neurotransmitters, trying to explain how systemic inflammation drives the brain crazy.